A Comunicação e a tangibilidade de sua avaliação - Yanaze, Mitsuru; Crepaldi, Ubaldo (Organicom, 2005)
This article discusses the decomposition of the objectives of Communication as a process of relationship. Through one brief revision of the literature and the presentation of some results of inquiries, it aims to contribute to the construction of a concept of Organization as a Communication process and to relate Communication actions to efficaciousness in the contribution to the achievement of the enterprise’s objectives.